A new species of Cantharellus (Cantharellales, Basidiomycota, Fungi) from subalpine forest in Yunnan, China - Shao, Shi-Cheng; Liu, Pei-Gui; Tian, Xiao-Fei; Buyck, Bart; Geng, Yan-Hong (Phytotaxa, 2016)
Cantharellus versicolor is described and illustrated as a new species based on morphological and molecular characters. The most significant features to distinguish the new species from other known Cantharellus are its extremely fleshy, turning gray after injury and with black floccose-fibrillose scales composed of thick-walled and irregular, erect hyphae on the pileus. It is described from the subalpine belt of Shangri-La, northwestern Yunnan, China. Phylogenetic analysis of the transcription elongation factor 1-alpha sequence data further support its systematic position in the subgenus Cantharellus and its description as a new species.